High-Reynolds number scale-resolving simulations of axisymmetric density current - Frantz,RAS; Farenzena,BA; Laizet,S; Silvestrini,JH (2019)
A three-dimensional implicit Large-Eddy simulation is presented for a cylindrical density current at a Reynolds number equal to 136,000, under the Boussinesq approximation for small density difference. The aim is to assess the ability of an implicit Spectral Vanishing Viscosity approach to numerically reproduce the main features of an axisymmetric release of heavy fluid into a light ambient fluid at high Reynolds numbers. Comparisons are made with experimental data and with numerical data at lower Reynolds numbers. It is found that the proposed approach is able to provide a detailed description of the structure of the current, information about the large-scale coherent structures, and to predict the evolution of the front velocity over the different stages of the current propagation.